ALIH KODE PADA ARTIS INDONESIA - DAHAR, JENDRI STEVINUS (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACT This skripsientitled Code Switching in Indonesian Artist: Sociolinguistic Analysis. The aim of this research is to identify, analyze and describe the code switching appeared in some Indonesian Artist Utterance and explain the reason for the phenomena mentioned above. The theories that are used in this research are by Hoffman (1991) and Fishman (1876) and this research used a descriptive method. The data was taken from Youtube. The result of this research shows that there are two kinds of code switching, Intra-sentential switching and Inter-sentential switching. The reasons of the code switching in artist through its speaker, listener or opponent saying, changing situations of the presence of the third person, the formal changes into the informal, change of subject, and its prestigious. Key Words: Sociolinguistic, Code Switching, Youtube, Indonesian Artist